Structural characterization of polycrystalline thin films by X-ray diffraction techniques - Pandey, Akhilesh; Dalal, Sandeep; Dutta, Shankar; Dixit, Ambesh (Journal of materials science. Materials in electronics, 2021)
X-ray diffraction (XRD) techniques are powerful, non-destructive characterization tool with minimal sample preparation. XRD provides the first information about the materials phases, crystalline structure, average crystallite size, micro and macro strain, orientation parameter, texture coefficient, degree of crystallinity, crystal defects etc. XRD analysis provides information about the bulk, polycrystalline thin films, and multilayer structures, which is very important in various scientific and material engineering fields. This review discusses the diffraction related phenomena/principles such as powder X-ray diffraction, and thin-film/grazing incidence X-ray diffraction (GIXRD) comprehensively for thin film samples which are used frequently in various branches of science and technology. The review also covers few case studies on polycrystalline thin-film samples related to phase analysis, preferred orientation parameter (texture coefficient) analysis, stress evaluation in thin films and multilayer, multiphase content identification, bifurcation of multiphase on multilayer samples, depth profiling in thin-film/ multilayer structures, the impact of doping effect on structural properties of thin films etc., comprehensively using GIXRD/XRD.